Gonorrhea Treatment Practices in the STD Surveillance Network, 2010–2012. Issue 1 (January 2015) - Kerani, Roxanne P.; Stenger, Mark R.; Weinstock, Hillard; Bernstein, Kyle T.; Reed, Mary; Schumacher, Christina; Samuel, Michael C.; Eaglin, Margaret; Golden, Matthew
<x xml:space="preserve">Abstract</x> Background Replacing oral treatments with ceftriaxone is a central component of public health efforts to slow the emergence of cephalosporin-resistant Neisseria gonorrhoeae in the United States; US gonorrhea treatment guidelines were revised accordingly in 2010. However, current US gonorrhea treatment practices have not been well characterized. Methods Six city and state health departments in Cycle II of the STD Surveillance Network (SSuN) contributed data on all gonorrhea cases reported in 101 counties and independent cities. Treatment data were obtained through local public health surveillance and interviews with a random sample of patients. Cases were weighted to adjust for site-specific sample fractions and for differential nonresponse by age, sex, and provider type. Results From 2010 to 2012, 135, 984 gonorrhea cases were reported in participating areas, 15, 246 (11.2%) of which were randomly sampled. Of these, 7, 851 (51.5%) patients were interviewed. Among patients with complete treatment data, 76.8% received ceftriaxone, 16.4% received an oral cephalosporin, and 6.9% did not receive a cephalosporin; 51.9% of persons were treated with a regimen containing ceftriaxone and either doxycycline or azithromycin. Ceftriaxone treatment increased significantly by year (64.1% of patients in 2010, 79.3% in 2011, 85.4% in 2012; P = 0.0001). Ceftriaxone use varied widely by STD Surveillance Network site (from 44.6% to 95.1% in 2012). Conclusions Most persons diagnosed as having gonorrhea between 2010 and 2012 in the United States received ceftriaxone, and its use has increased since the release of the 2010 Centers for Disease Control and Prevention STD Treatment Guidelines.